COMMUNICATIVE LANGUAGE TEACHING “CLT” IN TECHING SPEAKING HORTATORY EXPOSITION TEXTS TO THE SECOND YEAR OF SENIOR HIGH SCHOOL STUDENTS (RETAIN, 2015)
Abstract Communicative Language Teaching (CLT) aims broadly to apply the theoretical perspective of the communicative approach by making communicative competence the goal of language teaching and by acknowledging the interdependence of language and communication (Larsen-Freeman, 2000). CLT helped the students to get the main goal of learning language that was being able to communicate. Therefore, the students had more time to practice the foreign language that they learnt because CLT was emphasizing on learning to communicate through interaction in the target language. This study was conducted to find out the implementation of CLT in teaching hortatory exposition texts to the second year of senior high school students. Descriptive qualitative research was used by the researcher in conducting this study. It means that the result was described qualitatively without statistical calculation. The researcher chose some of instruments that could be used in this research. Those were observation checklist, field notes, and scoring rubric. The implementation of CLT in this study was conducted into two stages: pre-communicative activity and communicative activity. Those stages were in line with the theory stated by Littlewood (1981). Moreover, it proved that the students’ grammatical mastery was in the different levels although the students were in the same grade. Some of students were good in grammar during speaking class. However, the rests were low on it. In addition, the observer also found that the students who talked actively often made more grammatical mistakes. Keywords: CLT, Speaking, Hortatory exposition text. Abstrak Communicative Language Teaching (CLT) bertujuan untuk menerapkan pendekatan komunikatif secara perspektif teoritis dengan membuat kompetensi komunikatif dalam pengajaran bahasa dan dengan mengetahui saling ketergantungan bahasa dan komunikasi (Larsen-Freeman, 2000). CLT membantu siswa untuk memperoleh tujuan utama dari belajar bahasa yaitu mampu berkomunikasi. Oleh karena itu, para siswa lebih memiliki banyak waktu untuk berlatih bahasa asing yang mereka pelajari, karena CLT menekankan pada belajar untuk berkomunikasi melalui interaksi dalam bahasa. Penelitian ini dilakukan untuk mengetahui pelaksanaan dari CLT dalam mengajar teks hortatori eksposisi untuk murid kelas dua SMA. Teks deskriptif kualitatif digunakan oleh peneliti dalam melakukan penelitian ini. Itu berarti bahwa hasil di dikripsikan secara kualitatif tanpa adanya perhitungan statistik. Peneliti memilih beberapa instrumen yang dapat digunakan dalam penelitian ini. Mereka adalah observation checklist, field note, dan scoring rubric. Pelaksanaan yang dilakukan guru dalam penelitian ini terbagi dalam dua tahap: aktivitas pra-komunikatif dan aktivitas komunikatif. Tahap tersebut sejalan dengan teori yang dinyatakan oleh Littlewood (1981). Selain itu, terbukti bahwa penguasaan tata bahasa siswa berada di tingkat yang perbeda meskipun mereka berada di kelas yang sama. Beberapa siswa baik dalam penguasaan tata bahasa selama kelas berbicara. Namun, sisanya rendah. Selain itu, pengamat juga menemukan bahwa siswa yang berbicara aktif lebih sering membuat kesalahan tata bahasa. Kata Kunci: CLT, berbicara, Teks hortatory eksposisi.